Radiographic findings related to interlocking nailing: windshield-wiper effect, and locking screw failure - Durall, I.; Diaz-Bertrana, M. C.; Puchol, J. L.; Franch, J. (Veterinary and Comparative Orthopaedics and Traumatology, 2003)
The purpose of this paper is to describe two uncommon radiographic findings related to the use of interlocking nails (ILNs) fixation. The first one is a radiolucency located around the distal tip of the nail observed in three clinical cases. This radiographic sign was similar to one described in human medicine known as “windshield-wiper effect” and observed around the tip of the screw used for slipped capital femoral epiphysis in children, and also in association with intramedullary nail treatment. In one of our clinical cases, the radiolucency observed four weeks post-surgery completely disappeared two months later, unfortunately a follow-up radiograph was not available in the two other cases. The second complication is related to three screw-bendings observed in the centre of the nail in two clinical cases. In one case both proximal screws appeared to be radiographically bent, and non-union of the fracture was observed five months after surgery. The screws were in fact broken, instead of being bent, which we were able to determine in the second surgery. In the other clinical case, the screw appeared to be radiographically bent, but the fracture had healed. We could not confirm whether the screw was bent or broken because the owner refused to permit removal of the implant. When bone healing complications are detected, bent screws should be checked and suspected of being broken.
Keywords: Interlocking nail; windshield-wiper effect; implant failure